The impact of anatomical and spatial distance between responses on response conflict. - Wühr, Peter; Heuer, Herbert (Memory & Cognition, 2018)
Different features of objects can be associated with different responses, so that their concurrent presence results in conflict. The Simon effect is a prominent example of this type of response conflict. In two experiments, we ask whether it is modulated by the anatomical or spatial relation between responses. Predictions were derived from an extended variant of the leaky, competing accumulator (LCA) model proposed by Usher and McClelland (Psychological Review, 108, 550-592, 2001). The relation between responses was represented by the lateral-inhibition parameter of the model. For the anatomical distance between responses the expectations were largely confirmed, but not for spatial distance. First, the Simon effect was stronger when responses were performed with two fingers of the same hand than with different hands. Second, the Simon effect was larger only for responses with different hands at short reaction times and disappeared at long ones, whereas for responses with fingers of the same hand, the Simon effect was essentially the same for shorter and longer reaction times. This difference resulted in smaller variability of reaction times in noncorresponding than in corresponding conditions. The dependence of decision processes, as modelled by the LCA model, on the anatomical relation between responses supports the broad hypothesis that the accumulation of evidence on the state of the world is intricately linked with the activation of response codes, that is, the selection of the appropriate actions.